SEMIOTIC ANALYSIS OF BLACK PEOPLE’S DISCRIMINATION IN REBECCA HALL MOVIE “PASSING” - Khatimah, Khusnul (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study aims to investigate what types of discrimination are experienced by black people depicted in the